Heme promotes sexual conversion of Plasmodium falciparum in human erythrocytes - Flage, Bethany; Dent, Matthew R.; Tejero, Jesús; Amoah, Linda Eva; Ofori-Acquah, Solomon Fiifi (Frontiers in Malaria, 2023)
Between 2018 and 2020, the global population experienced a 55% increase in deaths attributed to the most prominent malaria-causing pathogen, Plasmodium falciparum. Transmission of P. falciparum from a human host to the mosquito vector is completely reliant on the formation of sexual stage gametocytes, which arise from asexually replicating parasites during the intraerythrocytic stage of infection. Defining specific factors that promote the formation of transmissible sexual stages from the disease-causing asexual stages is important for developing new malaria control methods. Malaria infection rates are known to be affected by genetic variation of the hemoglobin (Hb) protein, and epidemiological studies have shown that Hb variants may positively influence the production of sexual stage parasites. However, the mechanisms involved are poorly defined. Here, we show P. falciparum sexual conversion rates (SCR) are significantly higher in erythrocytes expressing Hb S compared to those that express Hb A. We then found parasitic enzyme-mediated digestion of Hb S to occur more rapidly than Hb A, suggesting an increased release of heme groups carried by each Hb subunit. Upon manipulating both intracellular and extracellular heme concentrations, we found significant increases in SCR, ultimately indicating heme acts as an inducer of sexual conversion (SC). As levels of both intracellular and extracellular heme are increased in individuals with Hb variants, we propose heme to be a contributing factor for increased sexual stage conversion observed in these populations. These findings support further investigation into how heme concentrations may be directly manipulated to prevent commitment to sexual-stage formation and ultimately disease transmission.